Resonance Effect on the Geosynchronous Orbit due to the Non-Zonal Geopotential - Jong-Uk Park; In-Sang Moon; Kyu-Hong Choi; Yong-Seok Choi (Journal of Astronomy and Space Sciences, 1990)
Resonance effect on the orbital elements of geosynchronous artificial satellite due to the non-zonal geopotential has been calculated. For the perturbation of a artificial satellite, perturbation effects due to the non-zonal geopotential is less than due to the J2 or Luni-Solar perturbation, but non-zonal harmonics resonance exist. So, we calculate the perturbation of geosynchronous artificial satellite orbit due to the non-zonal harmonics resonance. The effect on the orbit eccentricity of non-zonal harmonics resonance is represented by a phase plane plot of ec verse es. The evolution of mean longitude and semi-major axis are obtained.